RESULTS OF TECHNICAL INSPECTION OF A 120-METER-HIGH METEOROLOGICAL TRIANGULAR MAST - Burchenia С.; Dudiak Н.; Vikhot С. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The article discusses the results of a technical inspection conducted on a 120-meter-high metal triangular mast to determine the causes of its failure. The mast is situated in an area with a seismicity rating of 7 on the seismicity scale, according to DBN V.1.1-12:2014 for Construction in Seismic Areas of Ukraine. The terrain is mountainous, and the site is located outside a settlement on Mount Plai, in an open area. The width in the axes of the belt elements varies with height. The mast is constructed from factory-made elements with heights of 2.4 meters, 2.0 meters, and 1.5 meters, using flange connections, and is anchored by guy wires at 10 different levels. The structural system is a vertically oriented continuous spatial metal truss. The cross-section of the mast forms an equilateral triangle. Vertical belt elements consist of steel pipes with diameters of 60 mm and 48 mm, while the lattice is made of solid metal rods with diameters of 20 mm, 18 mm, and 16 mm. The stays are steel cables with a diameter of 10 mm. The spatial rigidity of the structure is achieved through the combined action of the truss body and the stays. During the technical inspection of the mast, a field survey methodology was employed to evaluate the load-bearing capacity of the structures. The inspection included several steps: familiarization with and study of the technical documentation related to the inspection object; preliminary inspection to assess the general condition of the structure and identify sections with visible defects; detailed visual inspection of visible defects, including damage to individual elements, deformations, cracks in components and joints, and any destruction; instrumental inspection utilizing specialized equipment and non-destructive testing methods, along with devices for linear measurements. Throughout the inspection, all elements of the mast were thoroughly examined, and conclusions regarding its failure were drawn based on these observations.